2018
DOI: 10.21037/jtd.2018.08.108
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage of a pancreatic metastasis from lung adenocarcinoma after osimertinib therapy

Abstract: Figure 1 Chest computed tomography (CT) at the time when the patient was referred to our hospital. CT showed a solitary 2.2 cm lung nodule in the right upper lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…7 Extrathoracic metastases are widely found in the bones, brain, liver, and adrenal glands. 8,9 Pancreatic metastases from lung adenocarcinoma have also been reported before, [10][11][12][13][14][15] but the pancreatic lesions in most cases were presented as synchronous metastases. Heterochronous metastases in the pancreas, which were relatively rare, might be easily confused with primary pancreatic malignancy since adenocarcinoma is also a mainstream phenotype of pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 78%
“…7 Extrathoracic metastases are widely found in the bones, brain, liver, and adrenal glands. 8,9 Pancreatic metastases from lung adenocarcinoma have also been reported before, [10][11][12][13][14][15] but the pancreatic lesions in most cases were presented as synchronous metastases. Heterochronous metastases in the pancreas, which were relatively rare, might be easily confused with primary pancreatic malignancy since adenocarcinoma is also a mainstream phenotype of pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 78%
“…In 2018 Kazuki Hayasaka, a scientist from Japan, reported 1 case of papilla of Vater bleeding after Osimertinib treatment for pancreatic metastases from lung adenocarcinoma, but there was no further analysis of the possible causes. 16 In 2013 Bai H, a scientist from China, reported 1 case of Erlotinib and gefitinib treatments result in gastrointestinal bleeding. 13 However, to date there have been no reports of Osimertinib being associated with gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no studies have been reported in which Osimertinib was associated with gastrointestinal bleeding. [10][11][12] The only drugs used for gastrointestinal bleeding associated with EGFR-TKI were Erlotinib and gefitinib. 13 Here we report a case of advanced NSCLC with diffuse colonic mucosal bleeding detected by colonoscopy after 1.5 years of Osimertinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Osimertinib might increase bleeding risk at metastatic sites of malignancy. Diffuse alveolar haemorrhage ( Forte and Sangani, 2019 ), subdural haemorrhage ( Yu et al, 2021 ) and metastatic pancreatic haemorrhage ( Hayasaka et al, 2018 ) have been previously reported. No case of intestinal haemorrhage was previously reported.…”
Section: Disscussionmentioning
confidence: 97%